-18=2(j+11)

Simple and best practice solution for -18=2(j+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=2(j+11) equation:



-18=2(j+11)
We move all terms to the left:
-18-(2(j+11))=0
We calculate terms in parentheses: -(2(j+11)), so:
2(j+11)
We multiply parentheses
2j+22
Back to the equation:
-(2j+22)
We get rid of parentheses
-2j-22-18=0
We add all the numbers together, and all the variables
-2j-40=0
We move all terms containing j to the left, all other terms to the right
-2j=40
j=40/-2
j=-20

See similar equations:

| 15=3(p-12 | | -4/5(x+5)=-12 | | 3(2x-1=5(3x-15 | | 3(n-11)=6 | | 0=300t-5t^2 | | 4(3x+2=11x+18 | | 3=-(r-17) | | 0.65*x=8.25 | | 4(3x+2=5(3x-2) | | p+22=821 | | 4(3x+2=5(3x-2 | | r−150=20 | | s+130=690 | | 6x+7=13x-13 | | 956=f+944 | | v+626=787 | | w+367=691 | | r+221=355 | | 8x+27=32 | | 3x-5/21+x=3x+5/3+1 | | X^2-14x-11=11 | | Y=-120x+600 | | 2{3w+8}=40 | | (15)(2/3x+10)=(15)(×/5+36/5) | | c(19-c)=2(6c+2)+3c | | 6-0.3x=1 | | 15=k/27 | | 4x-x^2+5=0 | | 5•2-x•5=5 | | 551=19q | | 27n=945 | | p/29=26 |

Equations solver categories